2014
DOI: 10.3109/09513590.2014.943716
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists in prevention of ovarian hyperstimulation syndrome

Abstract: The aim of this review is to analyze the efficacy of different dopamine agonists in the prevention of ovarian hyperstimulation syndrome (OHSS). Cabergoline, quinagolide and bromocriptine are the most common dopamine agonists used. There are wide clinical variations among the trials in the starting time (from the day of human chorionic gonadotrophin (hCG) to the day following oocyte retrieval); the duration of the treatment (4-21 days), the dose of cabergoline (0.5 mg or 0.25 mg orally) and in the regimens used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Therefore, the use of cabergoline is recommended and it is suggested that treatment be commenced on the day of hCG trigger at a dose of 0.5 mg for 8 days [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the use of cabergoline is recommended and it is suggested that treatment be commenced on the day of hCG trigger at a dose of 0.5 mg for 8 days [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cabergoline is an ergot derivative with high affinity for D 2 dopamine receptors, which cause inhibition of PRL secretion (Romagnoli et Short communication: The effects of cabergoline administration at dry-off of lactating cows on udder engorgement, milk leakages, and lying behavior al., 2009). In nonruminant animals, cabergoline has a much longer half-life (~70 h) than quinagolide (17 h), and it also has less adverse effects than quinagolide (Kasum et al, 2014). However, in cattle, half-life of cabergoline has been reported to be ~20 h (Velactis; European Medicines Agency, 2014).…”
Section: Short Communicationmentioning
confidence: 96%
“…It is interesting to note that 15 d after dry-off, serum PRL concentrations were still lower (P < 0.05) in CAB than in CTRL cows. The half-life of cabergoline has been reported to be about 70 h (Kasum et al, 2014) in dogs and mice and about 20 h in cattle (Velactis SPC Mexico; C646.2.03.E.0). The results herein showed a sustained decrease in serum PRL concentrations 15 d after injection, in line with studies in other species showing a persistent effect of cabergoline on serum PRL concentration (Ferrari et al, 1986;Mattei et al, 1988).…”
Section: Short Communicationmentioning
confidence: 98%
“…In addition, different administration regimens of Bromo are used to treat Parkinson's disease (Perez-Lloret and Rascol, 2010), as well as the ovarian hyperstimulation syndrome (Gomez et al, 2006;Kasum et al, 2014), although favorable outcomes related to these diseases have been achieved. The results of the present study suggest that alteration of the permeability of the BBB may be an adverse effect after prolonged treatment with the drug and in cases where Bromo completely inhibits PRL production.…”
Section: Discussionmentioning
confidence: 99%